Smartphone aiding in analysis of Hamman's sign. Issue 11 (19th November 2019) - Thakeria, Priyanka; Danda, Nita; Gupta, Anudeep; Anand, Dharmesh
Abstract : Hamman's sign refers to an unusual click that occurs in synchrony with heart sounds, and is pathognomonic for left-sided pneumothorax and spontaneous mediastinum. In this case, a 17-year-old man living in a rural area used his smartphone to record an audible clicking sound emanating from his thorax. This occurred following coughing episodes secondary to an upper respiratory tract infection. Initially, this prompted a request for an echocardiogram to exclude structural cardiac anomalies; however, Hamman's sign was also considered. This facilitated the timely diagnosis of pneumothorax to be made via a simple chest radiograph, one of the only imaging modalities available at the patient's rural health service. To promote awareness of this rare clinical phenomenon, this report also presents the patient's own sound recording of Hamman's sign and corresponding chest radiographs.